KAJIAN SIFAT FISIKA KIMIA TANAH INCEPTISOL DI BERBAGAI KELERENGAN DAN KEDALAMAN TANAH PADA AREAL PERTANAMAN KAKAO - Ida Suryani; Juni Astuti; Nurul Muchlisah (Fapetrik-UMPAR, 2022)
This study aims to examine some of the physical and chemical characteristics of the inceptisol soil on various slopes and soil depths in the cocoa planting area. The method used in this research is descriptive method by conducting surveys and taking soil samples based on land position, namely slopes of 3%, 15%, and 40% at depths of 0-25 cm and 25-50 cm, respectively. The results showed that the soil texture on all slopes and soil depths was clay texture. The percentage of clay in the upper layer (0-25 cm) was higher than that in the lower layer (25-50 cm) on the 3 and 40% slopes, while on the 15% slope the opposite occurred. The pH value of each slope and depth ranges from 4.52-5.35 with acid criteria. Bulk density on the slope of 3% and 40% on the top layer (0-25 cm) is lower than the bottom layer (25-50 cm), except for the 15% slope. The bulk density of the top and bottom layers is in the same range. Porosity and soil permeability decrease with the slope height both at the top soil depth (0-25 cm) and at the bottom depth (25-50 cm). Organic C, total N, available P and available K of each slope (3%, 15%, and 40%) decreased from the upper layer (0-25 cm) to the lower layer (25 50 cm).